Teachers Perception of the Utilization of Instructional Graphics Organizers Based on Gender (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates Teachers Perception of the Utilization of Instructional Graphics Based on Gender in public primary Schools in Obio/Akpor Local Government Area of Rivers State, Nigeria. Two research questions and two null hypotheses were used to guide the study. The study was a descriptive survey research. The population of the study was 676 teachers and the random sampling technique was used to get a sample size of 50 respondents. The instrument that was used for data collection was the Graphic Organizers Teachers’ Questionnaire (GOTQ). With a Reliability coefficient of 0.05. Mean and Standard Deviation were used to answer the research questions, while Independent Sample Test Statistics was used to test the hypotheses using Statistical Package for Social Science (SPSS, version 15.0). Findings from the study revealed that: There is a significant difference in the mean scores of teachers who uses graphic organizers in teaching basic science. There is no significant difference in the utilization of graphic organizers between male and female teachers when teaching basic science concepts. The study recommended among others, that graphic organizers should be used for teaching both concrete and abstract concepts to pupils at lower primary school level. Also, that, Professional and research organizations such as the Science Teachers’ Association of Nigeria (STAN), National Teachers‟ Institute (NTI) and The Nigerian Educational and Research Development Council (NERDC) that carryout seminars, workshops and conferences should incorporate themes / topics on graphics in their basic science education re-training programs for teachers at the Public Primary School level.